Implications of Rho GTPase Signaling in Glioma Cell Invasion and Tumor Progression - Fortin Ensign, Shannon P.; Mathews, Ian; Symons, Marc; Berens, Michael; Tran, Nhan L. (Frontiers in Oncology, 2013)
Glioblastoma (GB) is the most malignant of primary adult brain tumors, characterized by a highly locally-invasive cell population, as well as abundant proliferative cells, neoangiogenesis, and necrosis. Clinical intervention with chemotherapy or radiation may either promote or establish an environment for manifestation of invasive behavior. Understanding the molecular drivers of invasion in the context of glioma progression may be insightful in directing new treatments for patients with GB. Here, we review current knowledge on Rho family GTPases, their aberrant regulation in GB, and their effect on GB cell invasion and tumor progression. Rho GTPases are modulators of cell migration through effects on actin cytoskeleton rearrangement; in non-neoplastic tissue, expression and activation of Rho GTPases are normally under tight regulation. In GB, Rho GTPases are deregulated, often via hyperactivity or overexpression of their activators, Rho GEFs. Downstream effectors of Rho GTPases have been shown to promote invasiveness and, importantly, glioma cell survival. The study of aberrant Rho GTPase signaling in GB is thus an important investigation of cell invasion as well as treatment resistance and disease progression.